(untitled) (Chittagong University Journal of Biological Sciences, 2013)
Food and feeding habits of Gonialosa manmina were done by the analysis of 197 guts of the fish using both occurrence and point methods and also by the Index of preponderance. As per Index of preponderance, the preferred food items were graded as cladocerans (65.34%-1st), copepods (20.96%-2nd), miscellaneous (8.89%-3rd), rotifers (2.81% 4th) and bacillariophyceae (0.77% 5th). High feeding intensity was observed during pre and post spawning months. Significant (P<0.01) positive relationships were observed between the total length (TL) and total gut length (TGL) (TGL=2.09799TL0.89677, r=0.963, t=10.22), total length (TL) and stomach length (StL)(StL=0.18447TL0.7599, r=0.997, t= 39.92), and total length (TL) and intestine length (IL) (IL=0.99105TL1.0256, r=0.9854, t=16.37). Total fish length was slightly shorter than the gut length (1:1.31) and more than 91% animal nature gut contents confirmed that the fish was mainly a surface feeder zooplanktivore in Kaptai lake. DOI: http://dx.doi.org/10.3329/cujbs.v4i1.13386 The Chittagong Univ. J. B. Sci.,Vol. 4(1&2):53-61, 2009